Pembelajaran Bahasa Inggris yang Menyenangkan melalui Pemanfaatan Moodel Circuit Learning pada Siswa di SDK Roworeke 2 - Yuliani Sepe Wangge; Yasinta Oktafia Yeni; Maria Natalia; Maria Lito Bukan (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
English as an international language needs to be introduced early to elementary school students. However, first-grade students often have short attention spans and require enjoyable and active learning approaches. This Community Service Program (PkM) aimed to improve the understanding of basic English vocabulary through the use of engaging learning media, namely colorful origami paper. The program was conducted through a one-day intervention using fun and interactive methods such as singing, folding, coloring, and guessing games related to vocabulary themes (colors and objects). The result showed that students were enthusiastic and actively involved in the activities. Evaluation revealed that 80% of the students were able to correctly recall at least 5 new English words. This indicates that colorful origami can serve as an effective and appealing medium for English learning among first graders.